Assessing various administration strategies for dsRNA vaccine delivery: a concise review of VP15-WSSV research progress in tiger shrimp Penaeus monodon - Parenrengi, Andi; Lante, Samuel; Suryati, Emma; Rosmiati, Rosmiati; Sulaeman, Sulaeman; Herlinah, Herlinah; Andriani, Yosie (Faculty of Fisheries and Marine Universitas Airlangga, 2025)
Graphical Abstract Highlight Research 1. The dsRNA application should correspond to the developmental stages of shrimp2. Immersion method was commonly used for larvae for handling many individuals3. Injection technique effectively delivered dsRNA to cells but was unsuitable for large-scale4. Oral administration of pellet-enriched dsRNA was applicable to apply on shrimp larvae, juveniles, and broodstocks Abstract RNAi technology offers a novel powerful approach to silence gene expression by introducing double-stranded RNA (dsRNA) into the cell to degrade the mRNA at the post-transcriptional stage. An administration method of dsRNA delivery is one of the main considerations in applying the dsRNA vaccine for controlling pathogen infections. This mini-review was focused on the evaluation of three different methods (immersion, injection, and oral administration) of VP15-dsRNA vaccine delivery to the tiger shrimp post-WSSV challenge test. The immersion method was generally applied for the larval stage of tiger shrimp and seemed to be a simple technique for a large number of individuals in a small tank. The VP15-dsRNA application by immersion improved the survival of tiger shrimp larvae by 3.9% compared to the control groups. The injection technique was an effective way to deliver dsRNA to the cell, but it is difficult to apply in a large number of individuals or populations. The injection of VP15-dsRNA increased significantly the survival rate, proPO, and THC of tiger shrimp. A higher survival rate (75%) was exhibited in tiger shrimp injected with in vivo and in vitro VP15-dsRNA than in the control. Oral administration by pellet-enriched VP15-dsRNA was a useful way for larvae, juveniles, and broodstocks, but it has limitations since the pellet leaches into the water. The application of the VP15-dsRNA vaccine on the feed significantly enhanced the 26.7% higher survival rate compared to the control. The higher survival was also supported by a higher number of THC. The three VP15-dsRNA delivery methods provide potential approaches to increase tiger shrimp resistance to control pathogen infection